Mediación intercultural en el ámbito de la inmigración en el Ecuador y propuesta de creación de un centro de mediación intercultural - Terán Noboa, Santiago Ricardo (2012)
The thesis aims to demonstrate the readers the need to create and implement a new mediation model between cultures, called Intercultural Mediation. The proposed model will allow to clear up conflicts which can come out between Ecuadorian citizens and foreigners. First of all, the thesis begins showing the mediation process importance, its kindness, and the explanation of its procedures which will help the readers to assess how convenience is to apply it within Ecuadorian legislation. Also, in the first chapter of this thesis, the reader can find some definitions related to the word culture in addition to its elements and characteristics that will allow the readers to make a correct analysis in order to draw their own conclusions about the thesis topic